Disclosure and publication of information on the governance and ownership of joint-stock corporations in Europe (19th-early 20th centuries) - Johan Poukens (IBF - Institut für Bank- und Finanzgeschichte, 2020)
Corporate law increasingly paid attention to the disclosure and publication of information on the governance and ownership of joint-stock corporations. This paper on the one hand gives an overview of mandatory disclosure and publication requirements for joint-stock companies in the corporate legislation of Belgium, France, Germany, the Netherlands, Spain and the United Kingdom from the beginning of the nineteenth century until the interwar period. We argue that changes over time were consequence of a new approach to investor protection which coincided with transition to a concessionary regime to general incorporation and that differences between countries with different legal traditions were minimal. On the other hand, references to official publications which contained constitutional documents and information on governance and ownership are provided in an appendix.
Keywords: N01; N43; N44; 330